2014
DOI: 10.1158/0008-5472.can-14-0697
|View full text |Cite
|
Sign up to set email alerts
|

Armed Oncolytic Virus Enhances Immune Functions of Chimeric Antigen Receptor–Modified T Cells in Solid Tumors

Abstract: The clinical efficacy of chimeric antigen receptor (CAR)-redirected T cells remains marginal in solid tumors compared to leukemias. Failures have been attributed to insufficient T-cell migration and to the highly immunosuppressive milieu of solid tumors. To overcome these obstacles, we have combined CAR-T cells with an oncolytic virus (OV) armed with the chemokine RANTES and the cytokine IL-15, reasoning that the modified OV will have both a direct lytic effect on infected malignant cells and facilitate migrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
207
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(216 citation statements)
references
References 44 publications
4
207
1
4
Order By: Relevance
“…19,21,22 To overcome this barrier, a number of groups have combined CAR T cells with other therapies designed to modulate the tumor microenvironment including checkpoint inhibitors and oncolytic viruses. 36 Additionally, CAR T cells themselves have been modified by the incorporation of co-stimulatory endodomains such as CD28, 4-1BB, and OX40, 37,38 though our results suggest that this is likely insufficient to provide long term in vivo benefit at the tumor site ( Figure S1). Other modifications include the transgenic expression of Th1 cytokines to promote autocrine growth 36,[39][40][41] or the incorporation of a dominant-negative TGF-b receptor, which sequesters this tumor-produced immunosuppressive cytokine.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…19,21,22 To overcome this barrier, a number of groups have combined CAR T cells with other therapies designed to modulate the tumor microenvironment including checkpoint inhibitors and oncolytic viruses. 36 Additionally, CAR T cells themselves have been modified by the incorporation of co-stimulatory endodomains such as CD28, 4-1BB, and OX40, 37,38 though our results suggest that this is likely insufficient to provide long term in vivo benefit at the tumor site ( Figure S1). Other modifications include the transgenic expression of Th1 cytokines to promote autocrine growth 36,[39][40][41] or the incorporation of a dominant-negative TGF-b receptor, which sequesters this tumor-produced immunosuppressive cytokine.…”
Section: Discussionmentioning
confidence: 81%
“…36 Additionally, CAR T cells themselves have been modified by the incorporation of co-stimulatory endodomains such as CD28, 4-1BB, and OX40, 37,38 though our results suggest that this is likely insufficient to provide long term in vivo benefit at the tumor site ( Figure S1). Other modifications include the transgenic expression of Th1 cytokines to promote autocrine growth 36,[39][40][41] or the incorporation of a dominant-negative TGF-b receptor, which sequesters this tumor-produced immunosuppressive cytokine. 42,43 Our approach extends upon the dominant-negative receptor concept by inverting a soluble immunosuppressive signal present in the tumor microenvironment into one that is immunostimulatory (4/7 ICR).…”
Section: Discussionmentioning
confidence: 81%
“…Superior tumor cell killing with the combination of CAR T-cells and Ad5-D24 was recently reported to be associated with accelerated caspase pathways in human tumor cells. 30 However, upregulation of death receptors or costimulatory molecules on infected tumor cells (rendering tumor cells more sensitive to lymphocyte-mediated killing) was not observed. Speculatively, these mechanisms may play a role in hamster tumor cells, warranting further investigation of the in vitro setting, if the appropriate reagents can be generated.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Nishio and colleagues reported that adoptive T-cell therapy can be enhanced by oncolytic adenovirus armed with chemokine RANTES and cytokine IL15, thus improving the trafficking and survival of CAR T cells in an immunodeficient mouse model (33). Although the results from these authors are valuable, the lack of an immune system overlooks many key attributes of ACT.…”
Section: Discussionmentioning
confidence: 99%